2013
DOI: 10.1158/0008-5472.can-13-0742
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming the Chromatin Landscape: Interplay of the Estrogen and Glucocorticoid Receptors at the Genomic Level

Abstract: Crosstalk between estrogen (ER) and glucocorticoid (GR) receptors has been shown to contribute to the development and progression of breast cancer. Importantly, the ER and GR status in breast cancer cells is a significant factor in determining the outcome of the disease. However, mechanistic details defining the cellular interactions between ER and GR are poorly understood. We investigated genome-wide binding profiles for ER and GR upon co-activation, and characterized status of the chromatin landscape. We des… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
114
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(128 citation statements)
references
References 42 publications
12
114
2
Order By: Relevance
“…Similarly, GR is associated with SWI/SNF complexes, proteins involved in ATP-mediated nucleosome remodelling (reviewed elsewhere, King et al (2012)). Accordingly, GR activation using dexamethasone can increase binding of E2-induced ERa at proximal chromatin locations (Voss et al 2011, Miranda et al 2013. Very similar observations were made with regard to the PR (Grøntved & Hager 2012).…”
Section: Chromatin Accessibility Post-inductionsupporting
confidence: 70%
“…Similarly, GR is associated with SWI/SNF complexes, proteins involved in ATP-mediated nucleosome remodelling (reviewed elsewhere, King et al (2012)). Accordingly, GR activation using dexamethasone can increase binding of E2-induced ERa at proximal chromatin locations (Voss et al 2011, Miranda et al 2013. Very similar observations were made with regard to the PR (Grøntved & Hager 2012).…”
Section: Chromatin Accessibility Post-inductionsupporting
confidence: 70%
“…Release of glucocorticoids from the adrenal glands follows two superimposed temporal patterns: a daily (circadian) pattern and an hourly ultradian pattern (Lightman et al 2002Young et al 2004;Atkinson et al 2006;Lightman 2006;Droste et al 2008;Lightman and Conway-Campbell 2010;Walker et al 2012). The effects of GR activation are further influenced by the cell-specific chromatin landscape (Stalder et al 1980;John et al 2008John et al , 2011Biddie et al 2011;Siersbaek et al 2011;Mandrup and Hager 2012) and by the action of other transcription factors and chromatin modifiers Voss et al 2011;Miranda et al 2013b;Morris et al 2014) genome-wide. This reveals a complex and dynamic picture of the GR-mediated transcription regulation (Stavreva et al 2012;Miranda et al 2013a), which is still not fully appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ESR1 and RARA cistromes showed that ESR1 and RARA share very similar binding profiles, although whether the interaction is antagonistic or co-operative is still controversial (Hua et al 2009, RossInnes et al 2010. Likewise, cistromic profiling of ESR1 and GR in mouse mammary epithelial cell lines revealed significant co-operation of these two NRs, through an assisted loading mechanism, in which binding of one NR facilitates chromatin remodeling thereby enabling access to DNA for the other NR (Miranda et al 2013). Another study profiling ESR1 and GR genomic localization in MCF-7 cells revealed that, although GR co-occupies several ESR1-binding sites in cells treated with both E2 and dexamethasone, GR recruitment to these sites is associated with displacement of ESR1 leading to the repression of estrogen receptor-mediated transcriptional activation of target genes (Karmakar et al 2013).…”
Section: Combinatorial Control Of Gene Expression By Nrs In Breast Camentioning
confidence: 99%